Vocalizations of female frogs contain nonlinear characteristics and individual signatures. - Fang Zhang (PLoS ONE, 2017)
Anuran vocalization is sexually dimorphic, with males doing the bulk of vocalizing. Female vocalization is rare and has been observed in a handful of species, including the concave-eared torrent frog (Odorrana tormota). Females O. tormota have been reported to emit moderate-level calls to attract males. In contrast to males, female's vocal signals show no evidence of nonlinear phenomena (NLP). However, with females emitting calls so infrequently that this conclusion must be considered tentative in light of the limited supporting data. The present study was undertaken to test the hypotheses that their vocalizations: 1. may not be purely linear, 2. may contain individual signatures, similar to their male counterparts. We recorded 671 calls from six captive gravid females and found that their vocalizations are as complex as male calls, with numerous calls exhibiting complex upward/downward frequency modulations, and 39% of female calls containing at least one component of the NLP, i.e., subharmonics, deterministic chaos, frequency jump, or biphonation. Furthermore, females in captivity tend to call in bouts throughout the day and night, and the call rate varies hourly with a maximum of >10 calls per minute matching the maximum call rate in males. Similar to males, female vocalizations carry individual signatures, and all sound parameters analyzed differ significantly between individuals. This represents the first report ever showing that vocalizations of female anurans: 1. contain NLP, 2. carry individual signatures. Presence of signatures in both the male and female vocalizations opens up the possibility for males (and females) to distinguish individual frogs in both sexes acoustically, and thus their sound communication ability may be more advanced than previously thought.